Penilaian Status Keberlanjutan E-Ticketing Bus Trans Semarang Mendukung Kota Pintar dengan Pendekatan Multidimensional Scaling - Mahida, Masmian; Handayani, Wiwandari (Warta Penelitian Perhubungan, 2019)
Status Assessment of E-Ticketing Sutainability for Trans Semarang Bus to Support Smart City using Multidimensional Scaling Approaches: One of the public service facilities using IT in the transportation sector is the eticketing of the Trans Semarang Bus. E-ticketing is a cashless bus ticket payment with the aim to facilitate the service process. The implementation of E- ticketing Trans Semarang Bus engine technology sometimes experiences the obstacles due to crowded service conditions, non-conducive network and signals, so the e-ticketing machine is error and unable to quickly detect data balance. The service clerk has not been able to be technically competent to deal with problems that occur suddenly when the e-ticketing machine is in trouble. The aim of conducting research is to assess the sustainability status of e-ticketing Trans Semarang Bus, which is viewed from the dimensions of input, process, and output, in attempt to determine the factors/attributes that influence the sustainability of the e-ticketing Trans Semarang Bus. The research employed descriptive qualitative-quantitative method with Multidimensional Scaling analysis. This research is expected to be an input in the formulation of the smart city development strategy of Semarang City Government, especially in the transportation sector. The results of the research show the sustainability status of e-ticketing Trans Semarang Bus on the good conditions of input dimension because it is supported by an integrated service, device and technology-oriented roadmap; integrated IT system framework in terms of hardware, software and networks; and IT network infrastructure. The sustainability status of e-ticketing Trans Semarang Bus is in good condition in the dimensions of the process which is supported by collaboration and cooperation among stakeholders; operational financing includes IT professionals, operations, maintenance. Meanwhile, the output dimension has a fairly sustainable status. This might be caused by other factors that need to be comprehensively evaluated.Keywords : Sustainability, Bus Trans Semarang, smart city, multidimensional scaling. Salah satu fasilitas layanan publik yang menggunakan IT di sektor transportasi adalah e-ticketing Bus Trans Semarang. Eticketing merupakan pembayaran tiket bus cashless yang bertujuan untuk mempermudah proses pelayanan. Penerapan teknologi mesin e-ticketing Bus Trans Semarang terkadang mengalami kendala akibat kondisi pelayanan yang ramai serta jaringan dan sinyal yang tidak kondusif, sehingga mesin e-ticketing menjadi error sehingga tidak mampu mendeteksi data saldo dengan cepat. Secara kompetensi teknis, petugas pelayanan belum mampu mengatasi permasalahan yang terjadi secara tiba-tiba ketika mesin e-ticketing mengalami gangguan (trouble). Tujuan penelitian mengenai penilaian status keberlanjutan e-ticketing Bus Trans Semarang yang ditinjau dari dimensi input, proses, dan output adalah untuk mengetahui faktor/atribut yang berpengaruh terhadap keberlanjutan e-ticketing Bus Trans Semarang. Penelitian ini menggunakan metode deskriptif kualitatif-kuantitatif dengan analisis Multidimensional Scaling. Penelitian ini diharapkan dapat menjadi masukan dalam perumusan strategi pengembangan kota pintar Pemerintah Kota Semarang khususnya sektor transportasi. Hasil penelitian menunjukkan bahwa status keberlanjutan e-ticketing Bus Trans Semarang pada dimensi input dalam kondisi baik karena didukung dengan roadmap terintegrasi yang berorientasi pada service, device, dan teknologi; framework sistem IT yang terintegrasi dari sisi hardware, software, dan jaringan; dan infrastruktur jaringan IT. Status keberlanjutan e-ticketing Bus Trans Semarang pada dimensi proses dalam kondisi baik karena didukung kolaborasi dan kerjasama antar stakeholders; pembiayaan operasional yang mencakup profesional IT, operasi, pemeliharaan, pelatihan, dan konsultan; dan interoperabilitas platform IT pada sisi aplikasi dan service. Sedangkan dimensi output memiliki status cukup berkelanjutan. Hal ini kemungkinan dapat disebabkan oleh faktor lain yang perlu untuk dievaluasi secara komprehensif.Kata kunci :Keberlanjutan, Bus Trans Semarang, Kota Pintar, Multidimensional Scaling.